The Relationship between Poverty and Environmental Damage in Indonesia: A VECM Analysis - Wahyudi, Setyo Tri; Badriyah, Nurul; Nabella, Rihana Sofie; Sari, Kartika; Rahmawati, Amalia (Department of Development Economics, Universitas Sriwijaya, 2025)
This study investigates the relationship between poverty and environmental damage in Indonesia. This study consists time series data covering the period from 2000 to 2023, and utilized the vector error correction model. The short-run findings reveal that economic inequality exacerbates CO2 emissions, as affluent groups exploit resources and disadvantaged community resort to unsustainable practices. This is compounded by political and economic power weakening environmental regulations. Conversely, CO2 emissions exacerbate poverty, especially in rural areas reliant on natural resources, making them vulnerable to environmental shocks. A strong positive correlation exists between ecological footprint per capita and CO2 emissions, driven by resource consumption and fossil fuel reliance, though renewable energy adoption shows promise in mitigating emissions. In the long run, our findings align with the Environmental Kuznets Curve theory, suggesting that economic growth, supported by clean energy and sound environmental policies, ultimately leads to reduced environmental impact. These findings underscore the critical need for balanced strategies that simultaneously address poverty alleviation and promote ecological sustainability through inclusive policies and a transition to renewable energy.